Identification of Land Use Classes Using Sentinel 2A Imagery in Laloeha Village, Kolaka District: Identification of Land Use Classes Using Sentinel 2A Imagery in Laloeha Village, Kolaka District - Ramad Arya Fitra; Muhammad Adam Suni (MULTIPLE: Journal of Global and Multidisciplinary, 2023)
Land use in Laloeha Village Kolaka District continues to change. Mapping and identifying land cover types using the Maximum Likelihood method is more accurate than other methods. This research aims to analyze the capabilities of Sentinel 2A Imagery and the Maximum Likelihood classification method for mapping and identifying land use types in Laloeha Village in Kolaka District. This research was carried out from July to September 2023 and was carried out in 4 stages, namely the first stage of image pre-processing by carrying out the layer stacking process. The second stage is image analysis and classification. The third stage is carrying out a ground check, and the fourth stage is validation and accuracy testing. The value of the accuracy test results with Overall Accuracy (OA) is 88.75% which is in the good category. The results of the land cover classification obtained 7 land cover classes, namely land use is the plantation class covering an area of 827.91 ha or 37.76%, the secondary dry land forest class covering an area of 557.83 Ha or 25.44%, the shrub class covering an area of 323.40 or 14.75%, the agricultural class covering an area of 277, 46 Ha or 12.65%, the residential class is 174.27 Ha or 7.95%, the open land class is 19.83 Ha or 0.90% and the water body is 11.92 Ha or 0.54% of the area of Laloeha Village, Kolaka District